Beyond Patient Satisfaction: Positioning Responsiveness as a Strategic Lever in Hospital Marketing and Business Growth - Fitriadiansyah, Ricky; Firdaus, M Riza; Rifani, Ahmad; Usmiati (Journal of Scientific Insights, 2025)
While responsiveness is widely recognized as a component of service quality in healthcare, prior studies have largely treated it as a supporting operational variable rather than a core strategic asset. Existing literature often situates responsiveness within frontline interactions, neglecting its broader role in driving institutional differentiation, marketing effectiveness, and business growth particularly in emerging market contexts. This research addresses that gap by repositioning responsiveness as a strategic organizational capability that can be cultivated, measured, and leveraged. Drawing on the Resource-Based View and Dynamic Capabilities Theory, this study proposes a novel framework that situates responsiveness as both an intangible resource and a dynamic competency with high marketing value. Using empirical data from 160 inpatients at a newly accredited Islamic hospital in Indonesia, the study utilizes a SERVQUAL-based instrument and structural equation modeling to assess the influence of responsiveness on inpatient satisfaction. Findings reveal that responsiveness, defined through dimensions such as speed, staff presence, and clarity of communication, has the strongest positive effect on patient satisfaction and intention to return. This study contributes new insights by linking responsiveness to business strategy, branding, and market performance offering a theoretical and practical advancement over existing models. It further contextualizes responsiveness within Islamic healthcare settings, where moral and cultural expectations intensify its strategic relevance. The findings have implications for hospital leaders aiming to embed responsiveness into institutional systems to achieve sustained competitive advantage in resource-constrained, highly competitive environments.